Características del consumo de tabaco en estudiantes de enfermería de la Universidad de Antioquia (Colombia) (2010)
ABSTRACT: To describe the tobacco consumption characteristics in nursing students of the University of Antioquia. Methodology. 435 nursing student’s descriptive study. A self applied form was used to report the information of the study variables. Results. The life prevalence of cigarette consumption was 39.5%, (14.4% current and 25.1% former smokers), 15.4% of smokers are at high risk of nicotine addiction. One out of four smokers started the habit at university. During the last 12 months four out of five smokers have tried to quit smoking and three out of five have the intention to quit smoking. The smoking cessation rate was 63.8%. 98.2% of the students disagree with the fact that nurses smoke. Conclusion. Cigarette consumption among nursing students although is not of great magnitude, it is a problem that require special attention from the agencies responsible for the university’s welfare programs.